Socio-Cultural Foundations in Teacher Education: Fostering Egalitarianism Among Preservice Teachers in The Mathematics Classroom - K. Agbozo, Korsi; Agyei, Evelyn; D. Arthur, Yarhands (Golden Ratio of Social Science and Education, 2024)
The study investigates the impact of a new teacher education curriculum emphasizing cross-cutting approaches for equal and inclusive mathematics teaching. Following from this, this study aims to assess the impact preservice teachers said the programme had on their practices. Employing a qualitative approach, this case study involved interviews with five preservice teachers. The investigation focused on understanding how the curriculum assisted them in addressing egalitarianism in mathematics education. Findings indicated that preservice teachers gained insights into equity-oriented mathematics teaching, emphasizing equal accessibility. They encountered challenges and opportunities associated with inclusive mathematics instruction, navigating complex situations to ensure equal student achievement. The results also underscored their enhanced understanding of equality in mathematics education. The study draws conclusive insights from the results, emphasizing the importance of teacher education programmes in shaping preservice teachers' perspectives on egalitarian practices in the mathematics classroom. Implications: The research suggested that fostering egalitarianism in mathematics education necessitates active involvement from teacher educators. They should play a pivotal role in guiding preservice teachers to enact egalitarian practices during their practicum experiences.